If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x(60 + -3x) * 6 + 15 = 15x + 50 Reorder the terms for easier multiplication: 2 * 6x(60 + -3x) + 15 = 15x + 50 Multiply 2 * 6 12x(60 + -3x) + 15 = 15x + 50 (60 * 12x + -3x * 12x) + 15 = 15x + 50 (720x + -36x2) + 15 = 15x + 50 Reorder the terms: 15 + 720x + -36x2 = 15x + 50 Reorder the terms: 15 + 720x + -36x2 = 50 + 15x Solving 15 + 720x + -36x2 = 50 + 15x Solving for variable 'x'. Reorder the terms: 15 + -50 + 720x + -15x + -36x2 = 50 + 15x + -50 + -15x Combine like terms: 15 + -50 = -35 -35 + 720x + -15x + -36x2 = 50 + 15x + -50 + -15x Combine like terms: 720x + -15x = 705x -35 + 705x + -36x2 = 50 + 15x + -50 + -15x Reorder the terms: -35 + 705x + -36x2 = 50 + -50 + 15x + -15x Combine like terms: 50 + -50 = 0 -35 + 705x + -36x2 = 0 + 15x + -15x -35 + 705x + -36x2 = 15x + -15x Combine like terms: 15x + -15x = 0 -35 + 705x + -36x2 = 0 Begin completing the square. Divide all terms by -36 the coefficient of the squared term: Divide each side by '-36'. 0.9722222222 + -19.58333333x + x2 = 0 Move the constant term to the right: Add '-0.9722222222' to each side of the equation. 0.9722222222 + -19.58333333x + -0.9722222222 + x2 = 0 + -0.9722222222 Reorder the terms: 0.9722222222 + -0.9722222222 + -19.58333333x + x2 = 0 + -0.9722222222 Combine like terms: 0.9722222222 + -0.9722222222 = 0.0000000000 0.0000000000 + -19.58333333x + x2 = 0 + -0.9722222222 -19.58333333x + x2 = 0 + -0.9722222222 Combine like terms: 0 + -0.9722222222 = -0.9722222222 -19.58333333x + x2 = -0.9722222222 The x term is -19.58333333x. Take half its coefficient (-9.791666665). Square it (95.87673608) and add it to both sides. Add '95.87673608' to each side of the equation. -19.58333333x + 95.87673608 + x2 = -0.9722222222 + 95.87673608 Reorder the terms: 95.87673608 + -19.58333333x + x2 = -0.9722222222 + 95.87673608 Combine like terms: -0.9722222222 + 95.87673608 = 94.9045138578 95.87673608 + -19.58333333x + x2 = 94.9045138578 Factor a perfect square on the left side: (x + -9.791666665)(x + -9.791666665) = 94.9045138578 Calculate the square root of the right side: 9.741894778 Break this problem into two subproblems by setting (x + -9.791666665) equal to 9.741894778 and -9.741894778.Subproblem 1
x + -9.791666665 = 9.741894778 Simplifying x + -9.791666665 = 9.741894778 Reorder the terms: -9.791666665 + x = 9.741894778 Solving -9.791666665 + x = 9.741894778 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9.791666665' to each side of the equation. -9.791666665 + 9.791666665 + x = 9.741894778 + 9.791666665 Combine like terms: -9.791666665 + 9.791666665 = 0.000000000 0.000000000 + x = 9.741894778 + 9.791666665 x = 9.741894778 + 9.791666665 Combine like terms: 9.741894778 + 9.791666665 = 19.533561443 x = 19.533561443 Simplifying x = 19.533561443Subproblem 2
x + -9.791666665 = -9.741894778 Simplifying x + -9.791666665 = -9.741894778 Reorder the terms: -9.791666665 + x = -9.741894778 Solving -9.791666665 + x = -9.741894778 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9.791666665' to each side of the equation. -9.791666665 + 9.791666665 + x = -9.741894778 + 9.791666665 Combine like terms: -9.791666665 + 9.791666665 = 0.000000000 0.000000000 + x = -9.741894778 + 9.791666665 x = -9.741894778 + 9.791666665 Combine like terms: -9.741894778 + 9.791666665 = 0.049771887 x = 0.049771887 Simplifying x = 0.049771887Solution
The solution to the problem is based on the solutions from the subproblems. x = {19.533561443, 0.049771887}
| 7x^2+34x-5= | | 15u^2-34u+15=0 | | 7b+17-9b+15= | | 9a^3-18a^2-7a-16=0 | | 4x+17=33 | | 4x^3+6x^2-40=0 | | 3v^2+8v-3=0 | | 5x-16=49 | | 80t+4=100 | | 15a-60a=0 | | x^2+x+202=0 | | 8a^2-48a+64=0 | | Z=3x-4y | | 6y-7=55 | | 3(4+5m)-12+(-3m)= | | 34-2a=-8(2a-6) | | 5z+3=-22 | | 5n=3n+.26 | | 3x^2+1x+1=10 | | 6x^2+96x+384= | | x^2-1.5x-1=0 | | a^2-2a+1=0 | | 31x-31(1-x)=0 | | 5x+0.40x=0.30(x+5) | | 5y+3=-6y+4+12 | | (5x+1)(x-5)=0 | | -2+5x+7x^2=0 | | .5(4-2x)=-6 | | -5x-5=-45 | | -42=-2(1+4n) | | 2X-1=21 | | 2a^2+16a^2+30a= |